Combination therapy with spesolimab and apremilast for refractory generalized pustular psoriasis: a case report - Li, Yuwei; Li, Zhenyu; Hu, Xinhong; Cao, Tianyu; Liu, Ling (Frontiers in Medicine, 2025)
Generalized pustular psoriasis (GPP) is a rare, life-threatening neutrophilic dermatosis characterized by recurrent episodes of widespread sterile pustules, systemic inflammation, and potential multi-organ failure. We present a 75-year-old woman with a 10-year history of GPP refractory to conventional therapies, including cyclosporine, tripterygium glycosides, and acitretin. Following initial spesolimab infusions that controlled acute flares but failed to prevent relapse, a sequential therapeutic strategy was initiated: a single 900-mg intravenous dose of spesolimab followed by adjunctive apremilast (30 mg twice daily). Within 36 h, her fever subsided (from 39 °C to 36.5 °C), and pustules resolved completely within one week. Notably, apremilast monotherapy maintained sustained remission for 13 months after spesolimab discontinuation, with no adverse events observed. The patient reported significantly restored quality of life and satisfaction with the treatment. This case suggests that combining an anti-interleukin-36 (IL-36) inhibitor for acute control with phosphodiesterase 4 (PDE4) inhibition for maintenance may offer a promising strategy for refractory GPP, though larger studies are needed to validate this approach.